Análisis del personaje Audiovisual ´´El Profesor de la serie La Casa de Papel´´ desde una narrativa Fílmica. - Flores Pintado, Arelis Jimabel (2024)
This analysis focuses on unraveling the multiple facets of the character "The Professor" of the series "La Casa de Papel" from three narrative approaches: phenomenological, formal and abstract, with the aim of understanding its complexity and its impact on the plot. From the phenomenological perspective, the character's motivations, internal conflicts, evolution and character are explored; in addition, the relationship he has with his colleagues inside and outside his workplace will be explored. From the formal approach, roles and archetypes are examined, as well as the contribution of the character during the narrative process. Finally, from an abstract perspective, we analyze his influence as an actor in the development of the story, his planning, leadership and, above all, the manipulation of people and situations that the teacher carries out to achieve his objectives. It also proposes an integral methodology for the analysis of characters in audiovisual film products, in order to enrich the field of study of audiovisual narrative and provide a guide, which will serve as a tool for a deeper appreciation of cinematographic and television art. Keywords: The Paper House; The Professor; Heists; cinematic character.